Hybrid Digital-Analog Codes for Source-Channel Broadcast of Gaussian Sources Over Gaussian Channels - Prabhakaran, V M; Puri, R; Ramchandran, K (IEEE transactions on information theory, 2011)
The problem of broadcasting a parallel Gaussian source over an additive white Gaussian noise broadcast channel under the mean-squared error distortion criterion is studied. A hybrid digital-analog coding strategy which combines source coding with side information, channel coding with side information, layered source coding, and superposition broadcast channel coding is presented. When specialized to the open problem of broadcasting a white Gaussian source over an additive white Gaussian noise broadcast channel with bandwidth mismatch, which has been the subject of several previous investigations, this coding scheme strictly improves on the state of the art.